Spermatogonial deubiquitinase USP9X is essential for proper spermatogenesis in mice. Issue 2 (August 2017) - Kishi, Kasane; Uchida, Aya; Takase, Hinako M; Suzuki, Hitomi; Kurohmaru, Masamichi; Tsunekawa, Naoki; Kanai-Azuma, Masami; Wood, Stephen A; Kanai, Yoshiakira
Abstract : USP9X (ubiquitin-specific peptidase 9, X chromosome) is the mammalian orthologue of Drosophila deubiquitinase fat facets that was previously shown to regulate the maintenance of the germ cell lineage partially through stabilizing Vasa, one of the widely conserved factors crucial for gametogenesis. Here, we demonstrate that USP9X is expressed in the gonocytes and spermatogonia in mouse testes from newborn to adult stages. By using Vasa-Cre mice, germ cell-specific conditional deletion of Usp9x from the embryonic stage showed no abnormality in the developing testes by 1 week and no appreciable defects in the undifferentiated and differentiating spermatogonia at postnatal and adult stages. Interestingly, after 2 weeks, Usp9x -null spermatogenic cells underwent apoptotic cell death at the early spermatocyte stage, and then, caused subsequent aberrant spermiogenesis, which resulted in a complete infertility of Usp9x conditional knockout male mice. These data provide the first evidence of the crucial role of the spermatogonial USP9X during transition from the mitotic to meiotic phases and/or maintenance of early meiotic phase in Usp9x conditional knockout testes.